2014
DOI: 10.1007/s00216-014-8014-2
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein C metabolism in human infants and adult patients by stable isotope tracer and mass spectrometry

Abstract: Surfactant protein C (SP-C) is deemed as the surfactant protein most specifically expressed in type II alveolar epithelial cells and plays an important role in surfactant function. SP-C turnover in humans and its meaning in the clinical context have never been approached. In this study, we used mass spectrometry to investigate SP-C turnover in humans. We studied four infants and eight adults requiring mechanical ventilation. All patients had no lung disease. Patients received a 24-h continuous infusion of (13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…PS helps maintain normal pulmonary structures and functions via its pluripotent roles, such as decreasing alveolar surface tension, drying of alveolar tissues, preventing pulmonary edema, relaxing smooth muscles, participating in local immunity (defense), and improving the properties of slime. As the only cell that produces SP-C, type II alveolar epithelial cell can be specifically marked with SP-C (Roldan et al, 2014;Simonato et al, 2014). This study confirmed a significantly lowered expression level of SP-C mRNA and protein in VILI rats; the SP-C levels in these rats were restored by the combined administration of IL-10 and rhKGF-2.…”
Section: Discussionsupporting
confidence: 68%
“…PS helps maintain normal pulmonary structures and functions via its pluripotent roles, such as decreasing alveolar surface tension, drying of alveolar tissues, preventing pulmonary edema, relaxing smooth muscles, participating in local immunity (defense), and improving the properties of slime. As the only cell that produces SP-C, type II alveolar epithelial cell can be specifically marked with SP-C (Roldan et al, 2014;Simonato et al, 2014). This study confirmed a significantly lowered expression level of SP-C mRNA and protein in VILI rats; the SP-C levels in these rats were restored by the combined administration of IL-10 and rhKGF-2.…”
Section: Discussionsupporting
confidence: 68%
“…As expected, at CICU admission, HLHS patients had the highest postoperative requirement of inotrope support (VIS score 18 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22); Po0.001) and higher oxygenation index and lower PaO 2 /FiO 2 with respect to ASD/VSD patients (P = 0.02 in both). The median duration of mechanical ventilation was significantly longer in the HLHS group (P = 0.011 vs. TOF group; Po0.001 vs. ASD/VSD group) and in the TGA group (Po0.001 vs. ASD/VSD group) ( Table 1).…”
Section: Postoperative Clinical Data and Measurementssupporting
confidence: 73%
“…Antiserum anti-SP-B was raised in a rabbit using SP-B as an antigen isolated by Bond Elute NH 2 chromatography from a chloroform extract of a purified human surfactant. The purity of the antigen is documented in Simonato et al (20).…”
Section: Sample Analysismentioning
confidence: 99%
“…Together with the finding of lacking SP-B in all other reported cases of this genetic disorder (7,17,18,(24)(25)(26) and the successful rescue of SP-B-deficient knockout mice (27), the analysis of BALF for SP-B concentration appears diagnostically helpful when pediatric DPLD potentially including this rare condition are investigated. In this context, it must be recommended to sample BAL before exogenous surfactant is applied, as the latter usually contains both SP-B and SP-C whose in vivo half-lives may be very long (28)(29)(30). For the precise diagnosis of SP-B deficiency, sequencing of the gene is necessary.…”
Section: Discussionmentioning
confidence: 99%